2015
DOI: 10.1590/0104-07072015001220014
|View full text |Cite
|
Sign up to set email alerts
|

Family relations, peer influence, spirituality and drug use among students in one university in Kingston, Jamaica

Abstract: ABSTRACT:This study seeks to illuminate the relationship between family relations, peer influence, spirituality and drug use among students in one university in Kingston, Jamaica. A cross-sectional survey design was employed to collect quantitative data from 335 undergraduate university students, using self-report questionnaires. The sample consisted of 335 students (69 % male and 31% female) between the ages 18-24 years. 77.6 % of the sample reported drug use within the past year. A significant positive corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
1
2
0
2
Order By: Relevance
“…A cohesive family would essentially encourage its children to adhere to societal values. For such a reason, cohesive family relationships may play a significant role as protective factors against youth drinking [19]. e present study found significant association between consumption of spirits among male students and fathers' occupation.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…A cohesive family would essentially encourage its children to adhere to societal values. For such a reason, cohesive family relationships may play a significant role as protective factors against youth drinking [19]. e present study found significant association between consumption of spirits among male students and fathers' occupation.…”
Section: Resultssupporting
confidence: 53%
“…Miller and Cook [18] found that family environment influences alcohol consumption among adolescents. To the contrary, Gough et al [19] observed that having positive family relationships did not influence consumption of alcohol.…”
Section: Introductionmentioning
confidence: 92%
“…In 2015, decriminalisation permitted the possession of up to two ounces of marijuana,52 84 an amendment that is likely to have encouraged its use as being socially acceptable and ‘normalised’ in line with the use of other legal drugs 85 86. As a result, repeated exposure to substance-using friends and family members can directly influence an individual’s drug-seeking behaviour 87 88. In the present analysis, respondents who reported that friends or family members used illegal drugs like marijuana and became inebriated, were significantly more likely to report past month CPU.…”
Section: Discussionmentioning
confidence: 67%
“…Verificou-se ainda que entre os adolescentes que utilizavam algum tipo de droga, 26,4% afirmaram utilizar com a família. Por outro lado, observou-se para as meninas que quanto melhor é a avaliação da adolescente sobre o ambiente familiar menor é a tendência de que use bebidas alcoólicas, apontando a satisfação com o relacionamento na família como elemento fundamental na prevenção do consumo de álcool pelos adolscentes 12,38 .…”
Section: Métodounclassified
“…Pesquisa realizada com 335 estudantes entre as idades de 18-24 anos na Jamaica, mostrou que o álcool era a droga lícita mais utilizada pelos jovens nos últimos 24 meses, no entanto o uso desta droga não estava correlacionado a disfunções familiares, ao contrário do uso de drogas ilícitas. O estudo também apontou uma correlação negativa e significativa entre o uso de drogas lícitas e ilícitas com a presença de influências de pares positivos 12 . Assim, embora seja um fator de risco, considera-se que o uso de drogas lícitas como 'ponte' para o consumo de outras drogas não tem uma relação causal, mas de probabilidade, pois o consumo possui relação com o indivíduo e com o contexto em que ele se insere, podendo ou não o levar ao envolvimento com drogas ilícitas 10 .…”
Section: Introductionunclassified